Socially Engaged Art and Social Work: Reflecting on an Interdisciplinary Course Development Journey. Issue 1 (2nd January 2016) - Wehbi, Samantha; McCormick, Katy; Angelucci, Sara
ABSTRACT: This article shares key questions guiding our process of building interdisciplinary bridges between social work and art to contribute to social justice-oriented education. Through a focus on socially engaged art, we discuss the purpose and forms that these practices take and the role of the audience/participants when working for social change with communities. We then present a proposed course outline that brings social work and socially engaged art together. Our hope is that this discussion will guide others interested in working through interdisciplinary collaborations, as can be seen by the growing interest in the mix of art and social work in practice and education.